Application of artificial intelligence to employ mathematical relations between numbers and their ranks in information security - M.Ramadhan , Shatha Abdullah; Abdul Jabbar, Safaa Nayyef; M. Ramadhan, Obay Abdullah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The personal secret numbers of computers, portable devices, electronic protection systems and other security methods and digital encryption. In this paper, the mathematical relations between numbers and mattresses were discussed and highlighted. Artificial intelligence has been used to employ the properties that connect the numbers at intervals to be used in digital protection systems. These relationships were implemented in the field of information security through the use of MATLAB, and good results were obtained and the method was very effective.